Lojistik merkez olabilmesi açısından Erzurum’un swot analizi ile değerlendirilmesi - Yapraklı, Tevfik Şükrü; Ünalan, Musa (My University, 2016)
Lojistik merkez; ulusal ve uluslararası nakliye, lojistik ve dağıtım ile ilgili faaliyetlerin farklı işleticiler tarafından yürütüldüğü bölge olarak tanımlanmaktadır. Lojistik merkezler, ulaşım ağlarına göre konumları, bölgesel gelişimdeki rolleri, yakın çevrelerindeki ekonomik gelişmeler gibi kriterler üzerinden önemli merkezler haline gelmektedirler. Bu çalışmada, Erzurum’un lojistik merkez olabilmesi adına mevcut durumu SWOT analizi ile incelenmiştir. Yapılan değerlendirme sonucunda, Erzurum ilinin güçlü yönleri; karayolu, demiryolu, havayolu ulaşım ağlarına sahip olması, doğu-batı ana ekseni çerçevesinde enerji bakımından geçiş noktasında bulunması; zayıf yönleri, soğuk iklimi sebebiyle sanayinin yeterince gelişmemesi ve şehre ait lojistik master planının olmaması; fırsatları, 10. Kalkınma Planı çerçevesinde çekim merkezi haline getirilecek şehirler içerisinde yer alması ve Karadeniz bölgesi ile Güneydoğu Anadolu bölgesi arasındaki stratejik konumu; tehditleri, altyapı alanında yaşanılan eksiklikler ve bölge ülkelerinde yaşanan siyasi belirsizlikler olarak tespit edilmiştir. Ayrıca çalışma sonucunda, Erzurum’un lojistik merkez olabilmesi adına fiziksel ve kurumsal alt yapı alanında bazı iyileştirmeler yapması, lojistik bilgi sistemleri alanında gerekli teknolojik alt yapı sistemlerini kurması, üniversite özel sektör arasındaki işbirliklerinin artması gerektiği yönünde önerilerde bulunulmuştur. Logistic center is a region where is operating national and international shipping, logistics and distribution activities from different operators. Logistic centers are becoming important hubs because of some criteria such as location according to transport network, the roles in regional development, economic developments in immediate surroundings. In this study, the current position of Erzurum examined with SWOT analysis. As a result of evaluation, it was determined that Erzurum has important strengths and opportunities. The strengths of Erzurum are having highway, railway, airway and being located transit point in terms of energy within the framework of east-west main axis. The weaknesses of Erzurum are underdevelopment of the industry due to the cold climate and lack of master plan of logistics. The opportunities of Erzurum are taking place the city that will become center of attraction in the framework 10. Development Plan and strategic position between Black Sea region and Southeast Anatolia region. The threats of Erzurum are shortcomings on infrastructure area and politic uncertainties in region countries. Also as a result of this study, we proposed that Erzurum should do some improvements on physical and institutional infrastructure, benefit from information technologies, set up technological infrastructure in the field of logistic information, and increasing collaboration between university and private sector.

Logistic center is a region where is operating national and international shipping, logistics and distribution activities from different operators. Logistic centers are becoming important hubs because of some criteria such as location according to transport network, the roles in regional development, economic developments in immediate surroundings. In this study, the current position of Erzurum examined with SWOT analysis. As a result of evaluation, it was determined that Erzurum has important strengths and opportunities. The strengths of Erzurum are having highway, railway, airway and being located transit point in terms of energy within the framework of east-west main axis. The weaknesses of Erzurum are underdevelopment of the industry due to the cold climate and lack of master plan of logistics. The opportunities of Erzurum are taking place the city that will become center of attraction in the framework 10. Development Plan and strategic position between Black Sea region and Southeast Anatolia region. The threats of Erzurum are shortcomings on infrastructure area and politic uncertainties in region countries. Also as a result of this study, we proposed that Erzurum should do some improvements on physical and institutional infrastructure, benefit from information technologies, set up technological infrastructure in the field of logistic information, and increasing collaboration between university and private sector.
Evaulating of Erzurum with swot analysis in order to being logictic center
Bildiri - Yayımlanmış
Keywords: Erzurum; Swot analizi; Lojistik merkez